Added value of contrast enhancement boost images in routine multiphasic contrast-enhanced CT for the diagnosis of small (<20 mm) hypervascular hepatocellular carcinoma. Issue 160 (March 2023) - Yabe, Shinji; Sofue, Keitaro; Hori, Masatoshi; Maebayashi, Tomoki; Nishigaki, Megumi; Tsujita, Yushi; Yamaguchi, Takeru; Ueshima, Eisuke; Ueno, Yoshiko; Murakami, Takamichi
Highlights: We devised two types of CE-boost (LA-PV and PV-LA) images to enhance the contrast effect of hepatic arterial and portal venous perfusion more selectively. For hypervascular HCC lesions, the tumor-to-liver CNRs in CE-boost images (LA-PV: 6.4 ± 3.0; PV-LA: −3.3 ± 2.1) exceeded those in CE-CT (LAP: 3.2 ± 1.7; PVP: −1.1 ± 1.4) (both P <.001). Adding CE-boost images to multiphasic CE-CT yielded better diagnostic performance than multiphasic CE-CT alone for small (<20 mm) hypervascular HCC (FOM, 0.807 vs. 0.751, P <.001). Abstract: Purpose: To investigate the added value of contrast enhancement boost (CE-boost) images in multiphasic contrast-enhanced CT (CE-CT) for diagnosing small (<20 mm) hypervascular hepatocellular carcinoma (HCC). Materials and methods: This retrospective study included 69 patients (age, 74 ± 8 years; 52 men) with 70 hypervascular HCCs (<20 mm) who underwent multiphasic CE-CT (pre-contrast, late arterial phase [LAP], portal venous phase [PVP], and equilibrium phase). Two types of CE-boost images were generated by subtracting PVP from LAP (LA-PV) images and LAP from PVP (PV-LA) images to enhance the contrast effect of hepatic arterial and portal venous perfusion more selectively. Tumor-to-liver contrast-to-noise ratios (CNRs) in CE-boost images were compared with those in CE-CT images using the Wilcoxon signed-rank test. Two independent readers reviewed the imaging datasets: CE-CT alone and CE-CT with CE-boost images. The diagnostic performance of each dataset was compared using jackknife alternative free-response receiver operating characteristics (JAFROC-1). Results: The tumor-to-liver CNRs in the LA-PV (6.4 ± 3.0) and PV-LA (−3.3 ± 2.1) images were greater than those in the LAP (3.2 ± 1.7) and PVP images (−1.1 ± 1.4) ( p <.001 for both). The reader-averaged figures of merit were 0.751 for CE-CT alone and 0.807 for CE-CT with CE-boost images ( p <.001). Sensitivities increased by adding CE-boost images for both readers ( p <.001 and = 0.03), while positive predictive values were equivalent ( p >.99). Conclusion: Adding CE-boost images to multiphasic CE-CT can improve the diagnostic accuracy and sensitivity for small hypervascular HCC by increasing the tumor-to-liver CNR.